JURISDICTION OVER LATROCÍNIO (ROBBERY RESULTING IN DEATH) (CIPEEX, 2025)
This paper defines the jurisdiction for prosecuting and adjudicating latrocínio (Article 157 §3 of the Criminal Code), classifying it as an offence against property and therefore subject to bench trial despite the fatal outcome; by contrast, intentional crimes against life lie within the constitutional remit of the Jury Court. It aims to explain why latrocínio does not shift jurisdiction to the jury and to systematize criteria distinguishing the immediate legal interest protected—property in robbery with a fatal result—from the protection of life in intentional homicide. Methodologically, it adopts a doctrinal-normative and descriptive approach grounded in the statutory definition of the offence and the constitutional allocation of jury competence. The findings indicate that, in latrocínio, death is a consequence of robbery and the immediately protected interest is not life, which triggers the bench judge’s jurisdiction; the Jury Court is limited to intentional crimes against life (consummated or attempted homicide). It concludes that, although a death occurs, latrocínio must be prosecuted and tried before a single judge, preserving the proper constitutional distribution of jurisdiction.
Keywords: Jurisdiction; bench judge; jury court